2020
DOI: 10.3897/zookeys.932.50314
|View full text |Cite
|
Sign up to set email alerts
|

The megascolecid earthworms (Annelida, Oligochaeta, Megascolecidae) in the Phu Quoc island, Vietnam, with descriptions of three new species

Abstract: The megascolecid earthworms of the Phu Quoc island are intensively investigated. Twelve species in three genera (Lampito Kinberg, 1867, Amynthas Kinberg, 1867, and Metaphire Sims & Easton, 1972) are recorded. Of these, Metaphire doiphamon Bantaowong & Panha, 2016 is recorded for the first time in Vietnam, and three species are newly described, namely Amynthas catenatussp. nov., A. phuquocensissp. nov., and A. poropapillatussp. nov. An identification key to 12 megascolecid species is provided as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The new species has been previously identified as Metaphire anomala. It is widely distributed in Southern Vietnam (Thai et al 2004;Nguyen 2014;Nguyen et al 2017aNguyen et al , 2017bNguyen et al , 2019Nguyen et al , 2020. However, this species is very different from both the original description (Michaelsen 1907), and re-description of M. anomala from Myanmar (Gates 1925(Gates , 1972, Thailand (Bantaowong et al 2011) in the position of male pores, number and position of spermathecal pores, genital markings in male and spermathecal regions and body size.…”
Section: Remarksmentioning
confidence: 99%
See 2 more Smart Citations
“…The new species has been previously identified as Metaphire anomala. It is widely distributed in Southern Vietnam (Thai et al 2004;Nguyen 2014;Nguyen et al 2017aNguyen et al , 2017bNguyen et al , 2019Nguyen et al , 2020. However, this species is very different from both the original description (Michaelsen 1907), and re-description of M. anomala from Myanmar (Gates 1925(Gates , 1972, Thailand (Bantaowong et al 2011) in the position of male pores, number and position of spermathecal pores, genital markings in male and spermathecal regions and body size.…”
Section: Remarksmentioning
confidence: 99%
“…For example, earthworms on islands still have been poorly recognised, except some data in Nam Du (Michaelsen 1934), Con Son (Thai et al 2004), Lai Son, Hon Tre, Nam Du and Phu Quoc (Nguyen et al 2017a(Nguyen et al , 2020. Several species were also recently described from Lai Son Island and Phu Quoc Island (Nguyen et al 2017a(Nguyen et al , 2020. It is thus suggested that more intensive surveys in islands of Vietnam would bring more new taxa to discovery.…”
Section: Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…J o u r n a l P r e -p r o o f 9 Depurated M.californica was fixed with pins on a smooth foam and two pairs of spermathecal pores were located in the 7th to 9th lateroventral intersegment (Nguyen et al, 2020;Xu and Xiao, 2010). Dissected and gently tore the septa along the abdominal midline of worms from anterior to clitellum segments, separated out the seminal vesicles, then rinsed with ultrapure water to remove adhering mucus, finally fixed in 10% formaldehyde solution for 48h.…”
Section: Histology and Morphology Examinationmentioning
confidence: 99%